2020
DOI: 10.1002/ijgo.13082
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous magnesium sulfate in the management of severe pre‐eclampsia: A randomized study of 12‐hour versus 24‐hour maintenance dose

Abstract: Objective To assess the effectiveness of a 12‐hour versus 24‐hour intravenous maintenance dose of magnesium sulfate (MgSO4) in women with pre‐eclampsia, and the maternal and fetal outcomes. Methods This was a randomized controlled trial conducted at the labor ward complex of University College Hospital, Ibadan, Nigeria between May and August 2014. Pregnant women with severe pre‐eclampsia were randomized to receive a 12‐hour versus 24‐hour maintenance dose of MgSO4. Study outcomes were occurrence of seizures, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 18 publications
0
5
0
3
Order By: Relevance
“…No individual trial demonstrated a difference in the outcome of seizure between groups; however, the number of participants in each study was small. Another small study in Nigeria 28 ( n = 80) also compared 12‐h versus 24‐h regimens, with no seizure events in either group. Our study adds substantially to this literature due to our large sample size, which exceeds the combined participants of the meta‐analysis.…”
Section: Discussionmentioning
confidence: 99%
“…No individual trial demonstrated a difference in the outcome of seizure between groups; however, the number of participants in each study was small. Another small study in Nigeria 28 ( n = 80) also compared 12‐h versus 24‐h regimens, with no seizure events in either group. Our study adds substantially to this literature due to our large sample size, which exceeds the combined participants of the meta‐analysis.…”
Section: Discussionmentioning
confidence: 99%
“…18 The other analysis, by Sullivan et al, included RCTs with women with preeclampsia and identified nine articles; six were included in our study, and three were excluded (one for high risk of bias, one study reported the total time on magnesium sulphate that included the antepartum time and therefore lacked a group exposed to 24 hours of magnesium sulphate postpartum, and one trial included an experimental group that received different durations of postpartum magnesium sulphate). 8,[19][20][21] We therefore feel that our study is more comprehensive and clinically useful, because we included every trial including preeclampsia or eclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…Unwaha et al, en el 2020 en su estudio retrospectivo, analizo 80 gestantes en las que encontró hiporreflexia en el 52% y debilidad muscular en el 60%, con valor de P <0,01 lo que nos indica que es estadísticamente significativo (49). Saha et al, en el 2017 en su estudio prospectivo, analizo 50 gestantes en las que encontró únicamente hiporreflexia en el 65% con valor de P <0,01 lo que nos indica que es estadísticamente significativo (50).…”
Section: Desarrollounclassified